Impact Of Social Awareness Of Students’ Emotional Competency - Zihao, Liu; Kee, Chng Lay (South Asian Journal of Social Sciences and Humanities, 2024)
Purpose: The primary aim of this study is to examine the association between social awareness and the emotional competence of students. Self-awareness and social awareness are the independent variables of the study, while emotional competency is the dependent construct. Additionally, the research investigates the mediating impact of cognitive appraisal and self efficacy, as well as the moderating influence of personal well-being. The study is carried out in relation to the educational system of China. Students presently enrolled in institutions of higher education constituted the target population of the research. Method: The present investigation utilizes a quantitative methodology. The data was gathered through the administration of a survey questionnaire comprising closed-ended questions. The statistical software packages AMOS and SPSS were utilized in the analysis of the data for this study. Findings: The results of the study revealed a significant correlation between SA and both SAW and SE. The impact of CA on the efficacy of SA and SAW is also significant. A significant association exists between EC and the variables SA, SAW, and CA. However, the relationship between EC and SE is insignificant. While CA’s impact is relatively insignificant, SE assumes a substantial role in mediating the situation. Additionally, it was ascertained that the moderating effect of PWB had a significant statistical impact. Conclusion and Implications: The findings contribute to practical applications and theoretical frameworks both. In addition to identifying potential avenues for future research, the study has assessed its own limitations.